Pengaruh Edukasi Pola Makan Berbasis Flipped Classroom terhadap Pengetahuan tentang Anemia dan Indeks Massa Tubuh pada Remaja Putri di MTs 1 Pondok Pesantren Al-Karimi Gresik - Abidah, Sahlatul; Ariestiningsih, Eka Srirahayu; Mulyani, Endah (JGK: Jurnal Gizi dan Kesehatan, 2025)
Anemia is a common nutritional problem in adolescent girls, which can be influenced by diet and knowledge about nutrition. Innovative educational methods, such as the flipped classroom model, have the potential to improve understanding and influence body mass index (BMI). Objective: This study aims to analyze the effect of flipped classroom-based nutrition education on knowledge about anemia and BMI in adolescent girls at MTs 1 Pondok Pesantren Al-Karimi, Gresik. Method: This study used a quasi-experimental design with a pretest-posttest control group approach. The study population consisted of adolescent girls at MTs 1 Pondok Pesantren Al-Karimi, Gresik. The sample was selected using the total sampling technique, because the population was less than 100, making it possible to include all students who met the inclusion criteria. The instrument used to conduct the study was a questionnaire adopted from previous similar studies. The study was conducted at MTs 1 Pondok Pesantren Al-Karimi, Gresik, for a certain period. Instrument Analysis: Knowledge about anemia and BMI was measured using a validated questionnaire and anthropometric measurements. Data Analysis: processed data is then analyzed, so that the results of data analysis can be used as a basis for decision making in solving problems, the analysis in this study is univariate analysis and bivariate analysis with the help of computer applications, namely SPSS for Windows.